Institutional diversity in domestic banking sectors and bank stability: A cross-country study - Christopher F. Baum; Caterina Forti Grazzini; Dorothea Schäfer (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
This paper analyzes the causal relationship between institutional diversity in domestic banking sectors and bank stability. We use a large bank- and country-level unbalanced panel data set covering the EU member states' banking sectors between 1998 and 2014. Constructing two distinct indicators for measuring institutional diversity, we find that a high degree of institutional diversity in the domestic banking sector positively affects bank stability. The positive relationship between domestic institutional diversity and bank stability is stronger in times of crisis, providing evidence that diversity can help to absorb both financial and real shocks. In particular, greater institutional diversity smooths bank earnings risk in times of crisis. Our results are economically meaningful and offer important insights to the ongoing economic policy debate on how to reshape the architecture of the banking sector.
Keywords: G01; G20; G21; G28; 330; Institutional Diversity; Shannon Index; Gini-Simpson Index; Bank Stability; Financial Crisis; Bank Competition